2012
DOI: 10.1111/j.1540-8159.2012.03377.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bioimpedance Body Composition Analysis on Function of Implanted Cardiac Devices

Abstract: Despite the manufacturers' recommendation to avoid BIA in patients with ICDs, this study showed no evidence of any interference in 20 patients. Bioimpedance analysis might be safe in such patients, but further confirmatory studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
0
16
1
1
Order By: Relevance
“…Buch et al 8 investigated the impact of BIA measurement on ICDs in 20 patients with HF using one type of BIA monitor at 3 different frequencies (5, 50, and 500 kHz) and found no EMI 8 . Our study differs from this previous report in 2 main respects.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Buch et al 8 investigated the impact of BIA measurement on ICDs in 20 patients with HF using one type of BIA monitor at 3 different frequencies (5, 50, and 500 kHz) and found no EMI 8 . Our study differs from this previous report in 2 main respects.…”
Section: Discussioncontrasting
confidence: 52%
“…Indeed, EMI may lead to oversensing, resulting in potentially serious complications including inappropriate shocks and inhibition of pacing. To our knowledge, the risk of potential EMI was tested only in a single small study that required further assessment 8 . Therefore, we aimed to prospectively evaluate the potential risk of EMI between BIA and ICDs in a larger number of patients and in a setting where the risk of EMI was experimentally maximized.…”
Section: Introductionmentioning
confidence: 99%
“…46 A recent study found BIA to be safe for use with pacemakers and defibrillators, broadening its potential use in populations with advanced HF. 47 Preliminary data from a study by Thomas et al 48 that used BIA to assess body composition in 354 patients with HF compared the relative contributions of lean body mass (LBM) and body fat mass (BFM) to the obesity paradox. They found that higher fat mass is protective in HF and higher lean mass may be protective in HF but not significantly.…”
Section: Reliability Has Been Questionedmentioning
confidence: 99%
“…22 A recent study found BIA to be safe for use with pacemakers and defibrillators, broadening its potential use in advanced HF populations. 23 Visceral fat deposited around the heart is known as epicardial adipose tissue (EAT), which can be imaged with CT or MRI. Increased EAT is associated with insulin resistance, central adiposity, dyslipidemia, and decreased adiponectin levels from this biochemically active organ.…”
Section: Evidence For An Obesity Paradox In Hfmentioning
confidence: 99%